2017
DOI: 10.1002/uog.17403
|View full text |Cite
|
Sign up to set email alerts
|

Repeat measurements of uterine artery pulsatility index, mean arterial pressure and serum placental growth factor at 12, 22 and 32 weeks in prediction of pre‐eclampsia

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
(47 reference statements)
4
16
0
Order By: Relevance
“…The subsequent fall in UtA‐PI with advancing gestation is thought to result from decreasing impedance to the uterine blood flow as trophoblast invasion is eventually completed. However, we, and others, have demonstrated that there is a de‐novo increase in third‐trimester UtA‐PI in pregnancies that are at increased risk of HDP. Furthermore, de‐novo increase in UtA‐PI in the third trimester is also associated with FGR, stillbirth and adverse clinical outcomes, even in the absence of HDP.…”
Section: Introductionmentioning
confidence: 70%
“…The subsequent fall in UtA‐PI with advancing gestation is thought to result from decreasing impedance to the uterine blood flow as trophoblast invasion is eventually completed. However, we, and others, have demonstrated that there is a de‐novo increase in third‐trimester UtA‐PI in pregnancies that are at increased risk of HDP. Furthermore, de‐novo increase in UtA‐PI in the third trimester is also associated with FGR, stillbirth and adverse clinical outcomes, even in the absence of HDP.…”
Section: Introductionmentioning
confidence: 70%
“…Ocular Doppler assessments are also more amenable to use in an office setting rather than requiring a scheduled exam with an ultrasound technician. The latter is of particular relevance when considering the increasing utility of repeat and third‐trimester measurement of maternal hemodynamic assessment in later pregnancy in screening and diagnosis of PE. There is no study combining serum biomarkers with ophthalmic artery Doppler for the prediction of PE; however, given similar performance to uterine artery Doppler screening, it might be safe to expect equal effectiveness in combined Doppler/biochemical screening for PE.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms linking low maternal circulating PlGF levels with decreases in cord blood IGF-I and leptin levels are unclear. Low maternal PlGF levels are associated with placental insufficiency as indicated by Doppler measurement of uterine artery pulsatility index ( 24 26 ). Low maternal PlGF levels may be indicative of placental insufficiency with reduced nutrient transfer and oxygen supply across the placenta ( 4 ).…”
Section: Discussionmentioning
confidence: 99%